2018
DOI: 10.3390/en12010122
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Thermal Analysis of Multi-Layered Microchannel Heat Sink for Concentrating Photovoltaic Application

Abstract: Concentrating photovoltaic has a major challenge due to the high temperature raised during the process which reduces the efficiency of the solar cell. A multi-layered microchannel heat sink technique is considered more efficient in terms of heat removal and pumping power among many other cooling techniques. Thus, in the current work, multi-layered microchannel heat sink is used for concentrating photovoltaic cooling. The thermal behavior of the system is experimentally and numerically investigated. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The maximum solar cell temperature reached 65 • C at 0.01 m/s. Alsiyabi et al [6] investigated the performance of the CPV system at 500× using a microchannel heat sink. They reported that the maximum cell temperature reached 54 • C using four layers of a microchannel heat sink, which adds to the cost of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum solar cell temperature reached 65 • C at 0.01 m/s. Alsiyabi et al [6] investigated the performance of the CPV system at 500× using a microchannel heat sink. They reported that the maximum cell temperature reached 54 • C using four layers of a microchannel heat sink, which adds to the cost of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers showed that a multilayered channel heat sink technique is more reliable compared to many other cooling approaches with better heat transfer rate and lower operating cost. Multilayered microchannel heat sinks have been used by Al-Siyabi et al 30 for CPV cooling.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a great number of studies have been conducted utilizing innovative geometries [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], employing liquid coolants with excellent thermal features [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], and applying micro-pin-fins [ 42 , 43 , 44 ] in order to improve the capabilities of microchannel heat sinks (MCHS) removing the heat generated by electronic chips.…”
Section: Introductionmentioning
confidence: 99%
“…Soleimanikutanaei et al [ 31 ] carried out a numerical study of the heat transfer enhancement through utilizing transverse microchannels in heat sinks. Al Siyabi et al [ 32 ] conducted an experimental research on the performance of a multilayered microchannel heat sink. Deng et al [ 33 ] numerically examined the behavior of double-layered microchannel heat sinks with different cross-sectional shapes.…”
Section: Introductionmentioning
confidence: 99%